1989
DOI: 10.1128/mcb.9.8.3438
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of glucocorticoid- and cyclic AMP-induced genes in T lymphocytes.

Abstract: Glucocorticoids and cyclic AMP exert dramatic effects on the proliferation and viability of murine T lymphocytes through unknown mechanisms. To identify gene products which might be involved in glucocorticoid-induced responses in lymphoid cells, we constructed a XcDNA library prepared from murine thymoma WEHI-7TG cells treated for 5 h with glucocorticoids and forskolin. The library was screened with a subtracted cDNA probe enriched for sequences induced by the two drugs, and cDNA clones representing 11 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 34 publications
5
77
0
1
Order By: Relevance
“…GIR was originally identified as a stress-responsive element from the murine T-cell line WEHI-7TG and normal thymocytes treated with glucocorticoids and forskolin [3,10]. Mouse GIR mRNA was detected at high levels in the brain and thymus, and its distribution in brain was found to be enriched in the dorsal and ventral striatum, the forebrain limbic structures and the hypothalamic nuclei [22].…”
Section: Introductionmentioning
confidence: 99%
“…GIR was originally identified as a stress-responsive element from the murine T-cell line WEHI-7TG and normal thymocytes treated with glucocorticoids and forskolin [3,10]. Mouse GIR mRNA was detected at high levels in the brain and thymus, and its distribution in brain was found to be enriched in the dorsal and ventral striatum, the forebrain limbic structures and the hypothalamic nuclei [22].…”
Section: Introductionmentioning
confidence: 99%
“…The construction of oligo(dT)-primed and randomly primed ZAPII cDNA libraries, using RNA from WEHI-7TG cells treated for 5 h with dexamethasone (1 M) and forskolin (12 M), and the subtractive hybridization procedure used to identify induced genes have been described elsewhere (17). The pBluescript SK(-) plasmid containing cDNA encoding FKBP51 (clone 213) was excised from the ZAPII vector by using an in vivo excision protocol (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…The pBluescript SK(-) plasmid containing cDNA encoding FKBP51 (clone 213) was excised from the ZAPII vector by using an in vivo excision protocol (Stratagene). An approximately 500-nucleotide fragment from the 5Ј end of the 2.2-kb cDNA insert of clone 213 was isolated by restriction enzyme digestion with EcoRI and XhoI, labeled to 10 9 cpm/g with the Multiprime DNA-labeling kit (Amersham), and used as a hybridization probe for library screening as previously described (17). Two libraries, a murine thymus ZAP cDNA library (Stratagene) and a UniZAPII cDNA library prepared from poly(A) ϩ RNA isolated from WEHI-7TG cells treated with dexamethasone (1 M) and forskolin (12 M) for various time intervals (0 min, 15 min, 30 min, 1 h, 2 h, or 5 h), were screened to obtain full-length cDNAs corresponding to clone 213.…”
Section: Methodsmentioning
confidence: 99%
“…This is reflected in the repeated incidental selection of VL30 cDNA clones in substructive screening procedures aimed at selecting inducible genes. Thus, VL30 elements were selected as genes in which expression is tumed on after epidermal growth factor {EGFI stimulation of quiescent mouse embryo cells in culture {Foster et al 1982}; VL30 cDNAs were selected as growth-specific elements expressed in SV40-transformed, nonconfluent cells but not in the confluent, contact-inhibited parental cells {Singh et al 1985); VL30 cDNAs were picked up in a selective procedure aimed at identifying genes in lymphoid cells activated by glucocorticoids (Harrigan et al 1989); VL30 elements were shown to be activated by chemical carcinogens {Hsieh et al 1987), whereas other studies have demonstrated a dramatic (500-fold) induction of VL30 expression under conditions of anoxia {Anderson et al 1989).…”
mentioning
confidence: 99%